Relationship Between Severity of Trauma and Blood Alcohol Concentration in Road Traffic Accident Cases Admitted to the Emergency Department of Bursa, Turkiye - KILIÇ, Serbülent; DAYI, Merve; DAYI, Muhammed; TEKİN, Abdurrahman; Yüksel, Melih (Naif Arab University for Security Sciences, 2025)
Objective: The purpose of this study was to determine if blood alcohol content and trauma severity were related to patients who had been in road traffic accident. Methods: This study examined the medical records of patients that were admitted to the Department of Emergency Medicine of Yuksek Ihtisas Training and Research Hospital, Bursa city of Turkiye, as a result of road traffic accidents between 01/01/2022 and 01/08/2023. Results: Out of the 5279 car occupants, 121 used alcohol (2.2%), and 111 (91%) of them were males. The most common type of trauma in the cases was head trauma (n = 76, 62.8%), while 26 cases (21.5%) required major surgery. The mean blood ethanol level of the cases was 137,39 ± 95,03 mg/dl, the median Injury Severity Score (ISS) score was 3 (IQR, 25-75: 2-9), and the median Revised Trauma Score (RTS) score was 9 (IQR, 25-75: 4-4). A statistically significant difference was determined between the blood alcohol concentration of the cases and head trauma and upper extremity injuries [(p<0.05), (p=0.002)]. We note a correlation between blood alcohol concentration and age [(p<0.001, r = 0.416)]. Conclusion: Our study revealed that high blood alcohol concentrations in road traffic accident cases are associated with high morbidity and mortality.